1997
DOI: 10.1093/humrep/12.7.1393
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosalpinges adversely affect markers of endometrial receptivity

Abstract: While in-vitro fertilization (IVF) was initially developed in women with tubal factor infertility, recent clinical studies have suggested that the presence of hydrosalpinges lowers implantation and pregnancy rates. We postulated that these hydrosalpinges cause impaired endometrial receptivity. A total of 103 women with hydrosalpinges were prospectively evaluated, and compared with 55 infertile and 44 fertile controls. All women had endometrial biopsies during the window of implantation, analysed by conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
1
11

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(131 citation statements)
references
References 11 publications
3
116
1
11
Order By: Relevance
“…Although contradictory reports have been made, women with endometriosis have altered b3 expression either in the glandular epithelium or the endometrial vasculature , Lessey & Castelbaum 1998]). Finally, women with hydrosalpinges, an accumulation of fluid within the fallopian tube, showed reduced b3 levels (Meyer et al 1997).…”
Section: Integrinsmentioning
confidence: 95%
“…Although contradictory reports have been made, women with endometriosis have altered b3 expression either in the glandular epithelium or the endometrial vasculature , Lessey & Castelbaum 1998]). Finally, women with hydrosalpinges, an accumulation of fluid within the fallopian tube, showed reduced b3 levels (Meyer et al 1997).…”
Section: Integrinsmentioning
confidence: 95%
“…The slides were evaluated under a light microscope (Olympus BX51, Tokyo, Japan), and the staining intensity of the antibody was analyzed by a semiquantitative analysis HSCORE. 22 The HSCORE was calculated using the following equation: HSCORE¼SPi (i+1), where i was the staining intensity (1¼weak, 2¼moderate and 3¼strong), and Pi was the percentage of the positively stained cells for each intensity varying from 0 to 100%. The assessment of staining intensity and HSCORE were evaluated in a doubleblind condition by three independent observers who did not know the disease status of the samples.…”
Section: Immunohistochemistry For 5-methylcytosine (5-mc)mentioning
confidence: 99%
“…The flow of hydrosalpingeal fluid (HSF) into the endometrial cavity may lead to mechanical flushing of the embryos from the uterus (6). Meyer et al (7) have shown that HSF reduced endometrial integrins which may facilitate implantation. These integrins were restored to normal following the excision of the hydrosalpinges.…”
Section: Introductionmentioning
confidence: 99%